A nova rotulagem nutricional para alimentos embalados: principais modificações nos rótulos dos produtos alimentícios - (:unkn) unknown (Universidade Federal do Pampa, 2022)
To facilitate consumers' understanding of nutritional information on food labels, new nutrition labeling rules for packaged foods in Brazil were instituted. Collegiate Board Resolution - RDC No. 429/2020 and Normative Instruction - IN No. 75/2020 will come into force in 2022 and aim to cover gaps in current nutrition labeling legislation. The objective of this study was to carry out a brief bibliographic review regarding the legislation on food labeling, focusing on the new rules for nutritional labeling for packaged foods and the main changes that will occur in the labels of food products from their implementation. The study was conducted through a literature review through consultations in scientific journals and legislation published in the Official Gazette of the Union. The main changes were grouped into large groups: nutrition facts table, front nutrition labeling and nutrition claims. The main changes are in the models and formatting of the nutritional information table, in the presentation of nutritional information for 100 g of product, in the declaration of total sugars and added sugars, in the daily reference values for some nutrients (protein, total fat, saturated fat, trans fats, sodium and added sugars), on the front nutrition labeling statement (for foods high in added sugars, saturated fats and/or sodium) and on new nutrition claims. It is expected that such modifications will enable better readability and visibility of the information presented on the labels, so that the consumer can correctly understand all the information presented.
Keywords: Rótulo; Embalagem; Tabela nutricional; Rotulagem nutricional frontal; Alegação nutricional; Label; Packaging; Nutrition facts table; Front nutrition labeling; Nutrition claim; CNPQ::CIENCIAS AGRARIAS